2019
DOI: 10.9734/ajaees/2019/v30i130099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Capital on Poverty Alleviation among Fish Farming Households in Oyo State, Nigeria

Abstract: This study investigates the effect of social capital investment on poverty reduction among fish farming households of Oyo State, Nigeria. A multistage sampling technique was adopted in the selection of the respondents. Primary data were collected using a structured questionnaire from a representative sample size of 359 households in four local government areas representing the four agricultural zones, namely Ibadan-ibarapa, Oyo, Ogbomoso and Saki in Oyo State, Nigeria. The study used a multinomial logit regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
3
5
0
Order By: Relevance
“…Generally, the trend of effects of the control and social capital dimension variables on food security in this study agrees with results from some previous studies, e.g., Ahmed et al [85], Achida et al [89], Adepoju [90], Lutomia et al [91]. These studies either analyzed the separate effects of some control variables or their joint (with social capital dimensions) effects on food security or welfare.…”
Section: Social Capital Determinants Of the Food Security Status Of Csupporting
confidence: 92%
“…Generally, the trend of effects of the control and social capital dimension variables on food security in this study agrees with results from some previous studies, e.g., Ahmed et al [85], Achida et al [89], Adepoju [90], Lutomia et al [91]. These studies either analyzed the separate effects of some control variables or their joint (with social capital dimensions) effects on food security or welfare.…”
Section: Social Capital Determinants Of the Food Security Status Of Csupporting
confidence: 92%
“…The mutual benefits generated through social capital could alleviate poverty among people, if it's properly coordinated or marshalled through a proper channel. Social connection, one among the benefits, reduces poverty through joint efforts of poor households contributing other capitals like financial, human and physical to enhance their welfare condition (Adepoju, 2019). Although many researchers suggested that social capital networks could be a key instrument to reduce poverty (Adepoju and Oni, 2012;Adepoju, 2019;, the pathway in which social capital networks contribute to poverty reduction haven't been systematically researched.…”
Section: Introductionmentioning
confidence: 99%
“…Social connection, one among the benefits, reduces poverty through joint efforts of poor households contributing other capitals like financial, human and physical to enhance their welfare condition (Adepoju, 2019). Although many researchers suggested that social capital networks could be a key instrument to reduce poverty (Adepoju and Oni, 2012;Adepoju, 2019;, the pathway in which social capital networks contribute to poverty reduction haven't been systematically researched. Whereas, the prevailing economic situation in Nigeria attaches importance to social capital as a solution for poverty reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In other parts of the globe, substantial progress was made due to the quality of efforts from affected nations and other development partners (Beegle, 2016). However, in Nigeria, poverty across all indices of measurement has increased with both increases in population and the nation's economic status (Ucha, 2010;British Council Nigeria, 2012;Abur et al, 2013;Action Aid Nigeria, 2015;Taiwo & Agwu 2016;Wossen et al, 2019;Adepoju, 2019;Oladeebo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Poverty studies in the region over the years have concentrated on its determinants (Etim and Udoh, 2013;Abu and Soom, 2016;Omotesho et al, 2016;Adepoju, 2019;Nwibo et al, 2019). However, the assessment of poverty-alleviating strategies has not been prominent in these studies.…”
Section: Introductionmentioning
confidence: 99%